Effects of Supplementing Concentrate on Cumulative Gas Production of Ration-Based Natural Grass - Eva, Eva Icahyaningrum; Kusmartono; Mashudi; Ndaru, Poespitasari Hasanah (Faculty of Animal Science, Universitas Brawijaya, 2024)
This research aimed to evaluate the effect of supplementation with concentrate on the cumulative in vitro gras production of rations made from natural grass. Natural grass is the primary source of fibre in livestock diets, especially for ruminant animals, and thrives in tropical regions. The high fibre content in field grass can have a positive effect on the digestive process. The following treatments were applied: T1 (40% natural grass + 60% concentrate-C1), T2 (40% natural grass + 60% concentrate-C2), T3 (40% natural grass 60% concentrate-C3), and T4 (40% natural grass + 60% concentrate-C4). The experiment used a randomized block design (RBD) involving four treatments and three replications. The variables observed were cumulative gas production, potential of degradation (b) and rate of degradation (c) values. The results revealed that the treatments significantly affected (P<0.05) cumulative gas production, with the highest value occurring in the T5 treatment (155.6 ml/500 g DM), followed by the T4, T3, T2 and T1 treatments (147.8, 138.0, 129.0 and 91.6 ml/500 mg DM, respectively), and potential gas production; however, the treatments did not significantly affect the b and c values. It can be concluded that, based on the research results, the concentrate containing the highest proportion of tofu waste had the highest cumulative gas production.